2015
DOI: 10.1002/cbdv.201400272
|View full text |Cite
|
Sign up to set email alerts
|

Butane‐2,3‐dione: the Key Contributor to Axillary and Foot Odor Associated with an Acidic Note

Abstract: Human body odor, which contains several volatile organic compounds, possesses various odor qualities. To identify key volatile compounds responsible for the common unpleasant odors derived from human axillae and feet, the odor quality and intensity of 118 human axillae and feet were directly evaluated by sniffing, and odor compounds obtained from the subjects were identified. Furthermore, the sensory differences in odor intensity and quality with and without addition of butane-2,3-dione were evaluated by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…67 Carboxen-polydimethylsiloxane SPME fibers have been used in the extraction of volatiles from scoured and unscoured sheep wool. 69 Skin odors transferred to fabrics from the human axillae 26,70 and hands 71 have been extracted with divinylbenzene/carboxen/polydimethylsiloxane coated fibers.…”
Section: Evaluating Odor On Textilesmentioning
confidence: 99%
“…67 Carboxen-polydimethylsiloxane SPME fibers have been used in the extraction of volatiles from scoured and unscoured sheep wool. 69 Skin odors transferred to fabrics from the human axillae 26,70 and hands 71 have been extracted with divinylbenzene/carboxen/polydimethylsiloxane coated fibers.…”
Section: Evaluating Odor On Textilesmentioning
confidence: 99%
“…Body odor is mainly generated by bacterial metabolism and oxidation of sweat and lipids on the human skin. It consists of various volatile compounds such as short-chain fatty acids, ketones, alcohols, and aldehydes [ 1 , 2 , 3 ]. Recently, odorants are used as disease biomarkers to develop some non-invasively tools for diseases monitoring [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, odor-causing compounds vary on different body parts and on the same body parts of different individuals. The authors have previously reported that the axillary odor of Japanese men can be categorized into three major types: milk-like odor (type M; 57%) cumin-like odor (type C; 18%), and acid-like odor (type A; 16%) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Axillary odor can be quite strong and shows considerable interindividual variation. Hara et al 2015 evaluated the quality and intensity of axillary odor in healthy Japanese males. They found that most Japanese males 57% have a weak, milk-like odor, while some males 18% have a strong spicy odor.…”
Section: Introductionmentioning
confidence: 99%